2020
DOI: 10.1186/s40729-020-00275-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface sub-micrometer topography following oxalic acid treatment on bone quantity and quality around dental implants in rabbit tibiae

Abstract: Background To explore the effects of topographical modification of titanium substrates at submicron level by oxalic acid treatment on bone quality and quantity around dental implants in rabbit tibiae. Methods A total of 60 blasted CP-grade IV titanium dental implants were used. Twenty-eight control implant surfaces were treated with a mixture of HCl/H2SO4, whereas 28 other test implant surfaces were treated with oxalic acid following HCl/H2SO4 trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…The novel component of implant surface modification in the present study was the use of oxalic acid. In addition to the observations reported by Johansson et al (2012), Halldin et al (2016 and Kanai et al (2020) in a similar experiment reported that adding oxalic acid to a surface preparation consisting of a combination of blasting and acid treatment resulted in improved bone integration. The mechanisms behind the enhanced healing results from using the oxalic acid alone or together with hydrofluoric acid in the preparation of implant surfaces are not fully understood.…”
Section: Re Sultsmentioning
confidence: 66%
“…The novel component of implant surface modification in the present study was the use of oxalic acid. In addition to the observations reported by Johansson et al (2012), Halldin et al (2016 and Kanai et al (2020) in a similar experiment reported that adding oxalic acid to a surface preparation consisting of a combination of blasting and acid treatment resulted in improved bone integration. The mechanisms behind the enhanced healing results from using the oxalic acid alone or together with hydrofluoric acid in the preparation of implant surfaces are not fully understood.…”
Section: Re Sultsmentioning
confidence: 66%
“…The structure of the bone collagen does not differ from that which occurs in other connective tissues, but differs in the profile of the collagen cross-links 47 . The Picrosirus red (PSR) staining used in our work allows the visualization of thin-immature (green) type III collagen and thick-mature (red) type I collagen under polarized light 48 , 49 . In the available literature, there is a lack of information about the effect of caponization on the distribution of collagen fibers of the tibiotarsal bone.…”
Section: Discussionmentioning
confidence: 99%